Discretion and Accountability of Local Government in Administering Governance - Anwar Sadat (Journal of Governance, 2020)
This study aims to investigate the limit of the discretion used in administering governance and the forms of responsibility when legal deviations occur. As a government adhering to the Welfare state, the principle of legality took a maximum role insufficiently in serving the interests of the citizens. The discretion appeared as an alternative to fill the gaps and weaknesses in the application of the principle of legality (wetmatigheid van bestuur). Results showed that the implementation of public service decentralization was motivated by the devolution of power from central to local government. This study applied a purposive sampling technique and was analyzed by descriptive qualitative which began with the process of collecting data, simplifying data, presenting data, and drawing conclusions. The results revealed that the use of discretionary power by Government Officials was only able to be applied in particular cases in which the prevailing laws and regulations did not regulate them, or the existing regulations governing them was not clear and it was in an emergency / urgent situation for the public interest. The guidelines for the use of discretion were the General Principles of Good Governance. Meanwhile, the responsibility for discretionary decisions was classified into two, (1) as a job responsibility, and (2) as personal responsibility. As the job responsibility, if acting for / and on behalf of the position (ambtshalve) which there was no element of maladministration. As personal responsibility, if the use of authority was found an element of maladministration.